Jornal O Progresso de Ponta Porã (1920-1927): história, imprensa e jornalismo no sul de Mato Grosso - Abreu, Rafael Rondis Nunes de (2024)
The newspaper O Progresso de Ponta Porã was founded on February 22, 1920, by the then municipal steward, Militão Viriato Baptista. On October 10 of the same year, the lawyer fromParaíba José dos Passos Rangel Torres buys the newspaper along with its typography. The periodical published editions until December 11, 1927, as a result of the State of Siege decreed for Mato Grosso by Artur Bernardes (1922-1926) and due to the periodical's opposition to the government it was censored. The newspaper's circulation was interrupted from August 10, 1924 until July 4, 1926, upon returning after the State of Siege, Pedro Ângelo da Rosa took over management of the periodical. O Progresso was a weekly, always published on Sundays, arranged in 4 columns and in most editions it had 4 pages. It circulated in the southern region of Mato Grosso, between the municipalities of Bela Vista and Ponta Porã, including the settlement areas of Nhu Vera, Cabeceira do Apa, Rincão do Júlio, Dourados, Amambaí, Caarapó, Juti, Campanário, among others. In this work O Progresso de Ponta Porã was analyzed as an object of research through the methodological approach of discontinuity with the newspaper of the same name in Dourados. The objectives of this work were: to characterize the subjects involved in the construction of the periodical, identify the main published contents, demonstrate the role and impact of the newspaper's circulation in the Sul do Mato Grosso, describe the main sources and advertising revenues and contribute to the historiographical field of press history. Finally, O Progresso de Ponta Porã was one of the main press vehicles in Mato Grosso in the 1920s, with different language and content covered through notes, news and reports, in addition to being an indispensable source for understanding Mato Grosso in the first decades of the 20th century, he left an important legacy for Mato Grosso and Mato Grosso do Sul journalism.